Hydrogen incorporation into butter improves its microbial and chemical stability, biogenic amine safety, quality attributes, and shelf-life - Alwazeer, Duried; Bulut, Menekse; Ceylan, Mehmet Murat; Celebi, Yasemin; Kavrut, Enes; Cetintas, Yunus; Hayaloglu, Ali Adnan (Elsevier, 2024)
Butter is susceptible to chemical and biological degradation. Hydrogen (H2) and nitrogen (N2) gases and BHT were incorporated into the butter, packaged into polyethylene laminated aluminum bags, and stored at 4 degrees C for 90 days. The microbial counts, peroxide value (PV), titratable acidity (TA), acidity degree value (ADV), and conjugated dienes and trienes (CD and CT) were examined. The samples' color and biogenic amines, amino acids, and volatile profiles were analyzed. At the end of storage, microorganisms grew slower in the H2 samples than in the other groups. The highest values of fat deterioration were determined for the control, while the lowest values were for the H2- and BHT-incorporated samples. All biogenic amines (BAs) showed the highest values in the control, while the lowest ones were observed in the BHT samples, followed by H2 and N2. H2 incorporation into butter limited the spoilage microorganism growth, improved the color, restricted the formation of BAs (44-61%), increased the levels of some amino acids (Met and Lys), and didn't give an off-flavor. The physicochemical results showed that H2 extended the shelf life of butter by 30 days. H2 incorporation can help the dairy industry extend shelf life and maintain the product's quality and safety.
Keywords: Butter; Hydrogen gas; Nitrogen gas; Butylated hydroxytoluene; Quality attributes